2008
DOI: 10.1093/ajcn/87.1.223s
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic response and health—a systematic review and meta-analysis: the database, study characteristics, and macronutrient intakes

Abstract: Among GI studies, observed reductions in glycemic load are most often not solely due to substitution of high for low glycemic carbohydrate foods. Available carbohydrate intake is a confounding factor. The role of unavailable carbohydrate remains to be accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 56 publications
1
32
1
5
Order By: Relevance
“…Across countries, however, larger differences were found, particularly for fibre and alcohol; negative GI correlations were observed in Italy and Spain for fibre, and in the Netherlands, in the UK general population and Norway for alcohol. Apart from the inverse result for sugar that we shared with Schulz et al (2005), and the absence of a relation with fibre found by Livesey et al (2008) (although only true at the overall level), our results were quite different from those of earlier studies on nutrient correlates that reported inverse associations with total carbohydrates (Jonas et al, 2003;Scholl et al, 2004;Schulze et al, 2004;Schulz et al, 2005) and protein (Schulz et al, 2005). With regard to fat, some studies have found positive trends with total fat (Jonas et al, 2003;Scholl et al, 2004;Schulz et al, 2005), as well as a negative trend with animal fat (Buyken et al, 2001), across GI quintiles.…”
Section: Discussioncontrasting
confidence: 43%
“…Across countries, however, larger differences were found, particularly for fibre and alcohol; negative GI correlations were observed in Italy and Spain for fibre, and in the Netherlands, in the UK general population and Norway for alcohol. Apart from the inverse result for sugar that we shared with Schulz et al (2005), and the absence of a relation with fibre found by Livesey et al (2008) (although only true at the overall level), our results were quite different from those of earlier studies on nutrient correlates that reported inverse associations with total carbohydrates (Jonas et al, 2003;Scholl et al, 2004;Schulze et al, 2004;Schulz et al, 2005) and protein (Schulz et al, 2005). With regard to fat, some studies have found positive trends with total fat (Jonas et al, 2003;Scholl et al, 2004;Schulz et al, 2005), as well as a negative trend with animal fat (Buyken et al, 2001), across GI quintiles.…”
Section: Discussioncontrasting
confidence: 43%
“…It seems that nomads have a low proportion of carbohydrates in their total dietary energy, and our results showed that fasting glucose were lower in nomads. Since previous papers have reported that insulin secretion will not rise when there is a low glucose load 20) , the low glycemic load in nomads may have played a factor in elevated fasting insulin not resulting in an increase in the number of metabolic risk factors. Furthermore, nomads in Mongolia usually travel by horseback.…”
Section: Discussionmentioning
confidence: 97%
“…Further, the presence of indigestible carbohydrate such as fiber in food products may lower postprandial glycaemia and has been shown to reduce GI of a meal [34]. Therefore, it could has been assumed, that the presence of ingredients such as oligofructose in the HC formula diet may influence the glycemic response and may also contribute to a lower GI.…”
Section: Discussionmentioning
confidence: 99%